La regulación sobre la ley que rige el arbitraje - Ardalan Haghpanah; Nejad Ali Almasi (Ius Humani. Jornal do direito, 2018)
Determining the law applicable to arbitrability is of paramount importance because the procedures taken by the legal system are very different. In this way, some systems principally recognize any disputes eligible for referral to arbitration, while some other legal systems have put an emphasis on the general inapplicability of arbitrability to the disputes and only accepts it in a few exceptional cases. The remainder of legal systems have taken a position in the middle of these two theories. Therefore, it is clear that determining the applicable and governing law can also pinpoint the ultimate arbitrability (or not) of the case. The main challenge of this research is to examine the law governing the practice of arbitration and how proceeds the arbitrability at the courts of arbitration. At the end of this study, it will be known that there are several criteria for determining the law governing arbitrability, including the lex fori, the law of the parties’ agreement, the law of the place of enforcement of the award, and the law of one or both of the parties. By the way, today transnational law principles seems to gain more importance. Each of these criteria has its own advantages and disadvantages. Moreover, the norms of human rights have also led to developments in the recognition and enforcement of foreign arbitration awards, in such a way that the tenets of human rights (in the domain of the recognition and enforcement of foreign arbitration awards) have also led governments to recognize acquired rights in foreign countries.